‘THINK-HOME’: A PHILOSOPHICAL FRAMEWORK FOR MOVING SPORTS MANAGEMENT IN AFRICA INTO NEW FRONTIERS - Umeakuka, Okey A. (International Journal of Human Kinetics, Health and Education, 2023)
Sports management in Africa is still lagging behind those of the more advanced nations of the world. Lack of sound and relevant philosophical guide-post was implicated as one of the factors responsible for this unsatisfactory situation. This paper, therefore, recommended the “Think-Home” philosophy for African countries. According to this philosophy traditional physical education and sports activities which are consistent and relevant to Africa’s way of life should guide sports management decisions and actions. It is a call on African countries to rediscover themselves vis-à-vis their performances in global sports meets. This paper highlighted some of traditional physical education and sports activities in African contexts and then drew attention to colonial incursion as being responsible for Africa’s poor performance in international competitions. The paper also related excellence in specific sporting activities to some specific cultures. It was then concluded that it is only when African nations focus their sports development efforts on sporting activities that are consistent with their culture and environment that they can move sports management in their respective countries into new frontiers.